Ex vivo evaluation of a novel surgical guide on the accuracy of closing wedge osteotomies. Issue 8 (23rd May 2019) - Shamir, Shelly K.; Wolynski, Jakob G.; Duncan, Colleen G.; Puttlitz, Christian; Duerr, Felix M.
Abstract: Objective: To determine the influence of a novel surgical guide on the accuracy and technical difficulty of closing wedge osteotomies (CWO). Study design: Ex vivo experimental study. Sample population: Canine tibia models (n = 40). Methods: A 20° cranial CWO (CCWO) was created without (standard procedure; STCCWO) or with the aid of a novel wedge osteotomy guide (WOCCWO). Procedures were performed by diplomate (n = 4) and resident (n = 6) surgeons, with each performing 2 STCCWO followed by 2 WOCCWO. To prevent bias, surgeons were unaware of the study purpose until after completing the STCCWO. The wedges were evaluated by comparing the deviation from the 20° target angle, divergence of the 2 osteotomies (osteotomy divergence angle [ODA]), and measurements of the wedge height at the caudomedial cortex (CMC) and caudolateral cortex (CLC). Technique difficulty was explored through a surgeon questionnaire. Results: The WOCCWO resulted in smaller mean ODA (WOCCWO = 0.86°, SD ± 0.38°, P  < .001), and smaller mean difference between CMC and CLC (WOCCWO = 0.29 mm, SD ± 0.19, P  < .001) than for the STCCWO (4.22°, SD ± 2.16° and 1.39 mm, SD ± 0.65 respectively). Deviation from the target 20° wedge angle was greater after STCCWO (1.46°, SD ± 1.27°) than after WOCCWO (0.53°, SD ± 0.33°, P = .004). No difference was reported regarding the difficulty of the procedures, but resident surgeons stated that they were more likely to use the guide in a clinical setting compared with diplomates. Conclusion: The wedge osteotomy guide improved the accuracy of CCWO compared with standard technique. Clinical significance: The clinical significance of the differences detected in this study is unclear and warrants in vivo investigation.